تخطيط المنهاج وحاجات المتعلمين - فرحت هيثم; الأحمد عدنان; غانم نعيمة (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
Designing a syllabus should essentially be based on answers to a number of questions, which should also be used in writing materials as well as in classroom teaching and evaluation. A syllabus must do at least two things: it should specify both the content of the course of instruction and the order of the presentation of the content. This dual quality of the syllabus establishes its strong connection with language theories and teaching methods. Given this, the specification of the content and the order of its presentation are always informed by a language theory and a teaching method. This is why there are a number of approaches to syllabus design, reflecting the different learning theories and teaching methods. This paper is primarily concerned with the major issues or factors affecting syllabus design, especially ESP syllabus design, focusing on the students, their needs, and the situation in which learning takes place as well as on the major types of syllabi. يجب أن يعتمد تخطيط المنهاج أساساً على أجوبة لعددٍ من الأسئلة التي يتوجّب أن تُستخدم في المواد المكتوبة، وفي التعليم والتقويم أيضاً. وعلى المنهاج أن يفي بأمرين على الأقل، إذ يجب أن يحدد مضمون البرنامج التدريسي وتسلسل عرض المضمون. إن هذه الصفة المزدوجة للمنهاج هي التي تجعله مرتبطاً ارتباطاً وثيقاً مع نظريات اللغة وطرائق التدريس، ذلك لأن تحديد المضمون وتسلسل عرضه يعتمدان على نظرية أو طريقة ما. ولهذا يوجد عدد من الطرائق لتخطيط المنهاج تعكس النظريات التعليمية والطرائق التدريسية الم ختلفة. إن هذه الورقة تُعنى أساساً بالمسائل والعوامل الرئيسة المؤثرة في تخطيط المنهاج، خاصة منهاج اللغة الإنكليزية لأغراض خاصة، وتركّز على الطلاب واحتياجاتهم وعلى الحالة التي يتم التعلّم فيها، وكذلك على أنواع المناهج.